Penerapan Metode Profile Matching Sistem Pendukung Keputusan Demosi Karyawan (Studi Kasus: PT Nafasindo) - Daniel F S P Sitohang; Berto Nadeak; Putri Ramadani (STMIK Budi Darma, 2020)
One effort in the development of information technology today requires fast and accurate information in its implementation. in the assessment of the work ability of well-performing and poor employees with the support of a decision support system it produces one of the implementations of the development of information technology in improving the quality of the company's work. where the decision making process determines employee demotion is still done manually. still there are often a number of errors such as misdirection. Therefore, to make an assessment in making a decision to choose a decent demotion employee based on the assessment carried out in the field. Then the decision support system that will be built with a computerized system so that decision making is done quickly and accurately. For this decision support system, use the Profile Matching method or matching the demotion of employee demos with the profile of the employee assessed with the specified Criteria. Making an application program must be made carefully, so that it looks easy to understand and proven useful and useful for users. the system built can help PT. Nafasindo in determining the demotion of employees who are decent and can reduce errors in determining the demotion of employees